Atrophic C2C12 Myotubes Activate Inflammatory Response of Macrophages In Vitro - Cong Wu; Yishan Tong; Jiapeng Huang; Shuo Wang; Haruki Kobori; Ziwei Zhang; Katsuhiko Suzuki (Cells, 2025)
Background: Skeletal muscle wasting is commonly observed in aging, immobility, and chronic diseases. In pathological conditions, the impairment of skeletal muscle and immune system often occurs simultaneously. Recent studies have highlighted the initiative role of skeletal muscle in interactions with immune cells. However, the impact of skeletal muscle wasting on macrophage inflammatory responses remains poorly understood. Methods: To investigate the effect of atrophic myotubes on the inflammatory response of macrophages, we established two in vitro models to induce myotube atrophy: one induced by D-galactose and the other by starvation. Conditioned medium (CM) from normal and atrophic myotubes were collected and administered to bone marrow-derived macrophages (BMDMs) from mice. Subsequently, lipopolysaccharide (LPS) stimulation was applied, and the expression of inflammatory cytokines was measured via RT-qPCR. Results: Both D-galactose and starvation treatments reduced myotube diameter and upregulated muscle atrophy-related gene expression. CM from both atrophic myotubes models augmented the gene expression of pro-inflammatory factors in BMDMs following LPS stimulation, including Il6, Il1b, and Nfkb1. Notably, CM from starvation-induced atrophic myotubes also enhanced Il12b, Tnf, and Nos2 expression in BMDMs after stimulation, a response not observed in D-galactose-induced atrophic myotubes. Conclusions: These findings suggest that CM from atrophic myotubes enhanced the expression of LPS-induced pro-inflammatory mediators in macrophages.